The Roles of Information Presentation on User Performance in Mobile Augmented Reality Application - Nazri, N.I.A.M. (Springer Science and Business Media Deutschland GmbH, 2022)
Mobile Augmented Reality (AR) has an interesting and interactive method of presenting information because it is the combination of real and virtual environments. Thus, a large amount of information is required and some of the necessary information is not fit to the screen due to the small screen display. Hence, lead to user dissatisfaction and not getting the right and accurate information. This study herein aims to examine the roles and optimal combination of information presentation to improve user performance in mobile AR applications. A possible combination of information modalities is created and a study was conducted by comparing two different conditions:1) without sound and haptic feedback; 2) with sound and haptic feedback. Results showed the optimal combination of information modalities is with sound feedback and haptic feedback based on statistical analysis and user preferences. Moreover, the roles of information presentation indeed able to support visual information modality in the mobile AR application. Â© 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.